The Relationship between Waist Circumference and Waist-to-Hip Ratio with Risk of Cardiovascular Disease in Indonesia - Hastuti, Anung Puji; Widigdo, Dwi Ari Murti; Sarwono, Bambang; Supriyatno, Heru (Jurnal Keperawatan Soedirman, 2022)
Cardiovascular disease (CVD) is one of the non-communicable diseases which is the mayor leading cause of death in the world. One of the modifiable factors of cardiovascular disease is central obesity. Assessment of central obesity status was carried out by measuring waist circumference (WC) and waist-to-hip ratio (WHR). This study aimed to determine the relationship between WC and WHR with the risk of cardiovascular disease. This was an observational study with a cross-sectional design. There were 106 respondents selected using a convenience sampling technique. In this study, the risk of cardiovascular disease was calculated using the Jakarta Cardiovascular Score. The Spearman Rho’s was used as bivariate analysis for this study. The findings showed that WC and the risk of cardiovascular disease indicates a significant relationship with a moderate correlation (p <0.001 and r =0.467). Meanwhile, there was a significant relationship between WHR and the risk of cardiovascular disease (p<0.001 and r =0.385). Nurse may use this study result as an evidence to develop a preventive central obesity program.